2010
DOI: 10.2503/jjshs1.79.239
|View full text |Cite
|
Sign up to set email alerts
|

Production of Haploid Plant of ‘Banpeiyu’ Pummelo [Citrus maxima (Burm.) Merr.] by Pollination with Soft X-Ray-Irradiated Pollen

Abstract: To induce haploid plants in Citrus maxima (Burm.) Merr. 'Banpeiyu', we evaluated the effect of pollination with soft X-ray-irradiated pollen on fruit set and seed development, and carried out ovule culture. When 'Banpeiyu' pummelo pistils were pollinated with X-ray-irradiated pollen of 'Fukuhara' sweet orange [C. sinensis (L.) Osbeck], the exposure doses affected the fruit set. The number of seeds per fruit was also affected by the exposure dose, and tended to decrease as the dose increased; however, all devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 27 publications
(38 reference statements)
8
15
0
Order By: Relevance
“…From the earlier findings by different researchers on induction of haploid plants through irradiated pollen techniques it was confirmed that the best irradiation dose of pollen for induced parthenogenesis varies from crop to crop and species to species; Froelicher et al (2007) reported that 300 Gy was best for induction of haploid plants in mandarin, whereas doses between 25 and 50 Gy were found optimum for squash (Kurtar et al, 2002), and a dose of 1500 Gy gave the best results for haploid induction in kiwifruit (Chalak and Legave, 1997). Another interesting result obtained from this experiment was that haploid plants were obtained only from ovule cultures at 50 DAP; however, Yahata et al (2010) reported that the ovule culture at approximately 40 DAP seemed to be appropriate for haploid induction in Citrus. On the other hand, all the plantlets regenerated from in vitro culture of embryos excised from mature seeds were diploid.…”
Section: Ploidy Levelmentioning
confidence: 66%
See 3 more Smart Citations
“…From the earlier findings by different researchers on induction of haploid plants through irradiated pollen techniques it was confirmed that the best irradiation dose of pollen for induced parthenogenesis varies from crop to crop and species to species; Froelicher et al (2007) reported that 300 Gy was best for induction of haploid plants in mandarin, whereas doses between 25 and 50 Gy were found optimum for squash (Kurtar et al, 2002), and a dose of 1500 Gy gave the best results for haploid induction in kiwifruit (Chalak and Legave, 1997). Another interesting result obtained from this experiment was that haploid plants were obtained only from ovule cultures at 50 DAP; however, Yahata et al (2010) reported that the ovule culture at approximately 40 DAP seemed to be appropriate for haploid induction in Citrus. On the other hand, all the plantlets regenerated from in vitro culture of embryos excised from mature seeds were diploid.…”
Section: Ploidy Levelmentioning
confidence: 66%
“…al., 1990;Chalak and Legave, 1997;Musial and Przywara, 1998;1999), apple (Zhang and Lespinasse, 1991;De Witte and Keulemans, 1994;Höfer and Lespinasse, 1996), pear (Bouvier et al, 1993), European plum (Peixe et al, 2000), blackberry (Naess et al, 1998), sweet cherry (Höfer and Grafe, 2003), and Citrus (Froelicher et al, 2007;Aleza et al, 2009;Yahata et al, 2010), the induction mechanism of those haploid plants is not yet clear. It is therefore imperative to ascertain the hybridity of those in vitro-raised plantlets to confirm their genetic origin using a precise system.…”
Section: Hybridity Analysis Using Ssr Markersmentioning
confidence: 99%
See 2 more Smart Citations
“…Since then, haploids have been produced by anther culture (Germanà 2011, Hidaka et al 1979, Wang et al 2015, interploid hybridization (Oiyama & Kobayashi 1993), and pollination of irradiated pollen (Froelicher et al 2007, Yahata et al 2010. However, these haploids were very weak and grew more slowly than the original diploid plants.…”
mentioning
confidence: 99%